Violence against children perpetrated by peers: A cross-sectional school-based survey in Uganda - Wandera, Stephen Ojiambo (Child Abuse Negl, 2017)
Violence against children by peers is a global public health problem. We aimed to assess factors associated with peer violence victimization among primary school children in Uganda. We conducted multilevel multivariable logistic regression analyses of cross-sectional data from 3706 primary students in 42 Ugandan primary schools. Among primary school students, 29% and 34% had ever experienced physical and emotional violence perpetrated by their peers, respectively. Factors strongly associated with both physical and emotional violence were similar and overlapping, and included exposure to interparental violence, having an attitude supportive of violence against children from school staff, not living with biological parents, working for payment, and higher SDQ score. However, we found that younger age, sharing sleeping area with an adult and achieving a higher educational performance score, were specifically associated with physical violence. On the other hand, being female, walking to school, reporting disability and eating one meal on the previous day, were particularly associated with emotional violence. Interventions to reduce peer violence should focus on family contexts, school environments and those with poor socio-economic status may need extra support.